2023
DOI: 10.3390/toxins15090555
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Protective Effects of Quercetin on Aflatoxin B1-Induced Toxicity in Bovine Foetal Hepatocyte-Derived Cells (BFH12)

Marianna Pauletto,
Mery Giantin,
Roberta Tolosi
et al.

Abstract: Aflatoxin B1 (AFB1) induces lipid peroxidation and mortality in bovine foetal hepatocyte-derived cells (BFH12), with underlying transcriptional perturbations associated mainly with cancer, cellular damage, inflammation, bioactivation, and detoxification pathways. In this cell line, curcumin and resveratrol have proven to be effective in mitigating AFB1-induced toxicity. In this paper, we preliminarily assessed the potential anti-AFB1 activity of a natural polyphenol, quercetin (QUE), in BFH12 cells. To this en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…Differentially expressed gene analysis showed that quercetin treatment affected lipid homeostasis, inflammation, immune processes, and carcinogenesis. 80 Quercetin was also found to inhibit AFB 1 -induced cytotoxicity in bovine mammary epithelial cells by upregulating expression of GSTA1 which mediated the GSH conjugation of the AFBO. 65 AFB 1 can bind to human serum albumin (HSA), which is detrimental to the metabolism of AFB 1 and reduce the elimination rate of AFB 1 .…”
Section: Luteolinmentioning
confidence: 96%
See 1 more Smart Citation
“…Differentially expressed gene analysis showed that quercetin treatment affected lipid homeostasis, inflammation, immune processes, and carcinogenesis. 80 Quercetin was also found to inhibit AFB 1 -induced cytotoxicity in bovine mammary epithelial cells by upregulating expression of GSTA1 which mediated the GSH conjugation of the AFBO. 65 AFB 1 can bind to human serum albumin (HSA), which is detrimental to the metabolism of AFB 1 and reduce the elimination rate of AFB 1 .…”
Section: Luteolinmentioning
confidence: 96%
“…In addition, quercetin directly affected AFB 1 metabolism by inhibiting the phase I enzyme activity in bovine fetal hepatocyte-derived cells, thereby inhibiting AFB 1 -mediated cytotoxicity and lipid peroxidation. Differentially expressed gene analysis showed that quercetin treatment affected lipid homeostasis, inflammation, immune processes, and carcinogenesis . Quercetin was also found to inhibit AFB 1 -induced cytotoxicity in bovine mammary epithelial cells by up-regulating expression of GSTA1 which mediated the GSH conjugation of the AFBO .…”
Section: Multiple Phytochemicals Against Afb1 Toxicitymentioning
confidence: 97%
“…siamensis could inhibit DNA adduct formation and reduce metabolic activation of AFB1 to mitigate AFB1 toxicity in hepatoma cells [108,110]. Besides, quercetin could reduce AFB1-induced lipid peroxidation and reverted cytochromes P450 variations to show its mitigation capability in the liver [111]. Recently, Elbasuni et al also proved that Chlorella vulgaris could mitigate hepatic aflatoxicosis [111].…”
Section: Mycotoxin Mitigationmentioning
confidence: 98%
“…Besides, quercetin could reduce AFB1-induced lipid peroxidation and reverted cytochromes P450 variations to show its mitigation capability in the liver [111]. Recently, Elbasuni et al also proved that Chlorella vulgaris could mitigate hepatic aflatoxicosis [111]. They found that Chlorella vulgaris mitigated AFB1-induced oxidative stress and inflammatory condition after three week treatment [112] On other hand, curcumin and silymarin have been studied to have the capability to provide cytoprotection against toxicity induced by FB1 and specially to reduce ROS formation after 48h treatment in porcine kidney-15 cells [113].…”
Section: Mycotoxin Mitigationmentioning
confidence: 99%